Exercise-Mediated Browning of White Adipose Tissue: Its Significance, Mechanism and Effectiveness - Mu, Wang-Jing; Zhu, Jie-Ying; Chen, Min; Guo, Liang (International journal of molecular sciences, 2021)
As a metabolic organ, adipose tissue plays an important role in regulating metabolism. In adults, most adipose tissue is white adipose tissue (WAT), and excessive expansion of WAT will lead to obesity. It is worth noting that exercise can reduce the fat mass. There is also a lot of evidence that exercise can promote the browning of WAT, which is beneficial for metabolic homeostasis. Multiple factors, including reactive oxygen species (ROS), metabolites, nervous system, exerkines and lipolysis can facilitate exercise-mediated browning of WAT. In this review, the roles and the underlying mechanisms of exercise-mediated browning of WAT are summarized. The effects of different styles of exercise on the browning of WAT are also discussed, with the aim to propose better exercise strategies to enhance exercise-mediated browning of WAT, so as to promote metabolic health. Finally, the different reactivity of WAT at different anatomical sites to exercise-mediated browning is reviewed, which may provide potential suggestion for people with different fat loss needs.